2009
DOI: 10.1128/jvi.00289-09
|View full text |Cite
|
Sign up to set email alerts
|

The First Virally Encoded Cytochrome P450

Abstract: The genome sequence of the giant virus Acanthamoeba polyphaga mimivirus revealed the presence of two putative cytochrome P450 (CYP) genes. The product of one of the two predicted CYP genes (YP_143162) showed low-level homology to sterol 14-demethylase (CYP51) and contained a C-terminal polypeptide domain of unknown function. YP_143162 expression (without an N-terminal membrane binding domain) in Escherichia coli yields a CYP protein which gives a reduced CO difference maximum at 448 nm and was formally demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 10 publications
2
76
0
1
Order By: Relevance
“…1 and S2), but our search for NAT genes in amoebozoa retrieved only one short EST from Acanthamoeba castellanii (Table S2), bearing limited similarity to the mimivirus NATs. Interestingly, the mimivirus genome has been reported to harbor two putative cytochrome P450 genes [16] which, together with the putative NAT genes identified here, could represent ancient forms of xenobiotic metabolizing enzymes.…”
Section: Nats In Protists and Associated Large Dna Virusesmentioning
confidence: 88%
“…1 and S2), but our search for NAT genes in amoebozoa retrieved only one short EST from Acanthamoeba castellanii (Table S2), bearing limited similarity to the mimivirus NATs. Interestingly, the mimivirus genome has been reported to harbor two putative cytochrome P450 genes [16] which, together with the putative NAT genes identified here, could represent ancient forms of xenobiotic metabolizing enzymes.…”
Section: Nats In Protists and Associated Large Dna Virusesmentioning
confidence: 88%
“…The first viral P450 (CYP5253A1) was discovered in the Mimivirus genome and is fused at its C terminus to a protein of unknown function but containing several post-translational modification sites (phosphorylation, myristoylation, and glycosylation) (98,99). Recent studies showed that the Saccharopolyspora erythraea glycosyltransferase enzyme EryCIII, which produces erythromycin D (from the substrates thiamine diphosphate-D-desosamine and 3-␣-mycarosylerythronolide B), is activated by the addition of the protein EryCII, with which it forms a heterotetrameric (2:2) complex (63).…”
Section: Non-redox Partner-p450 Fusion and Partner Proteinsmentioning
confidence: 99%
“…Cytochrome P450 enzymes (CYPs) are iron (Fe) containing heme-proteins, which are found in most living organisms, including eukaryotes, archaea, bacteria, and viruses [1][2][3][4]. The enzymes catalyze a broad range of reactions such as hydroxylation [5], decarboxylation [6], epoxidation [7], reductive dehalogenation [8], amine/oxygen dealkylation [9], and sulfoxidation [10], employing molecular oxygen and electrons [e.g.…”
Section: Introductionmentioning
confidence: 99%